Muatan Ideologi Iklan Global Pada Tayangan Media Televisi di Indonesia - Agung Eko Budiwaspada (ITB Journal Publisher, LPPM ITB, 2007)
This study tries to uncover the existence of ideological values that are present in the global advertisement in Indonesia, by focusing on how these ideological values are present in the communication ideas of global advertisements. It is aimed to respond to the whole factual problem using a series of analysis. At first, the meaningful expression of objects are identified, especially those that are related to the thoughts, perceptions, concepts, and objectives of global expressions in the advertisements. The interpretation norm of semiotic approach was employed to identify the ideological values of those global advertisements in Indonesia. Results indicate that global advertisements in Indonesia are loaded with ideological values. It is reflected in the appearances of those advertisements, including the swinging values of consumerism, cultural imperialism, stereotyping global lifestyles, perfectionism, and decontextualism. Although these embedded values are-somewhat-contradicting Indonesian values, they may emerge through dis-culturation, inculturation, and acculturation processes as there are no adequate efforts to make the public aware. This may lead to a big sacrifice that we all have to endure, and that is the emergence of high-cost culture.